Analysis Of Internet Consumption Behavior And Interest Of Gen Z: A Case Study Of Indonesia Comnets Plus Company Provider Users In Ciledug Subdistrict - Ferdiyansah, Muhammad Ridho; Pradana, Mahir (eProceedings of Management, 2025)
This study aims to analyze the internet consumption behavior of Generation Z in Ciledug District who use ICON+services. As a generation born in the digital era, Generation Z has unique preferences in using internet services, whichaffect the dynamics of the internet service provider market in Indonesia. This study uses a quantitative method withdata obtained through a questionnaire-based survey. Data were analyzed using the Partial Least Square (PLS) methodto test the relationship between independent and dependent variables. The results of the study indicate that internetconsumption behavior has a significant influence on user satisfaction with ICON+ services. These findings provide apractical contribution for ICON+ in developing better service strategies to meet the needs and expectations ofGeneration Z, while also providing a theoretical contribution to the study of internet consumption behavior. Keywords: Internet Consumption Behavior, Generation Z, User Satisfaction, ICON+, Partial Least Square